Federated Malay States original correspondence 1950-1951 (Bangi : Universiti Kebangsaan Malaysia, 1971)
Surat-surat berkaitan hal-hal seperti perundangan; keadaan tentera;'weekly Intelligence Summary';'Monthly CID survey of crime'; dll.